The Psychological Implications of Automated Insulin Delivery Systems in Type 1 Diabetes Care - Nefs, Giesje (Frontiers in Clinical Diabetes and Healthcare, 2022)
Automated insulin delivery (AID) systems have brought important glycemic benefits to type 1 diabetes management. The present paper provides an overview of their psychological implications. Trials and real-world observational studies report improvements in diabetes-specific quality of life, with qualitative work describing reduced management burden, increased flexibility and improved relationships. Not all experiences are positive, however, evidenced by dropping algorithm use soon after device initiation. Apart from finance and logistics, reasons for discontinuation include technology frustrations, wear-related issues and unmet glycemic and work load expectations. New challenges include distrust in proper AID functioning, overreliance and deskilling, compensatory behaviors to override or trick the system and optimize time in range, and concerns related to wearing multiple devices on the body. Research efforts may focus on incorporating a diversity perspective, updating existing person-reported outcome measures according to new technology developments, addressing implicit or explicit health professional bias in technology access, examining the merits of incorporating stress reactivity in the AID algorithm, and developing concrete approaches for psychological counseling and support related to technology use. An open dialogue with health professionals and peers about expectations, preferences and needs may foster the collaboration between the person with diabetes and the AID system.